Modern features of the development of the theory of "innovative waves" - Golovash, B. E.; Golovash, L. V (Ways to Improve Construction Efficiency, 2019)
Current trends in the development of the world economy indicate the increasing role of innovation in the economies of developed countries. Nowadays, scientific and technological progress is accelerating in the world, the intensification of scientific and technological links and, as a consequence, the intellectualization of the main factors of production. In this case, development occurs cyclically under the influence of many factors. The purpose of the study is to determine the theoretical basis of cyclical development of the economy, to identify the modern features of the development of the theory of "innovation waves" and to analyze the essence and main laws of innovation development, to evaluate the place of Ukraine in international innovation processes and to identify the main directions of activization of Ukraine. . The article deals with the basic principles of the theory of cyclical development of the economy of M. Kondratiev and the theory of innovative waves in the economy of J. Schumpeter. The development of these theories in modern scientific thought is analyzed. Features of development of innovative K-waves are investigated. The theoretical prerequisites for the formation of K-waves are reviewed, and the sixth K-wave is identified, which is associated with the spread of nanotechnologies and biotechnologies, their integration with information technologies, technologies based on artificial intelligence, and which should bring with it significant innovations in existing forms of economic activities The focus is on innovation, as the driving force behind the evolutionary economic development of the state. It is determined that one of the most favorable moments for the beginning of large-scale innovative technological changes is the period of exit from the stagnation stage to the stage of economic recovery, in the phase of which Ukraine is now. This opportunity should be taken, including the synchronization of innovation policy measures with the sixth wave of the K-wave world cycle development, which should help to significantly accelerate the pace of socio-economic development of Ukraine. The need for activation of the country's innovation policy is emphasized.